1993
DOI: 10.1007/bf01246357
|View full text |Cite
|
Sign up to set email alerts
|

He-Ne laser irradiation affects proliferation of cultured rat Schwann cells in a dose-dependent manner

Abstract: Schwann cell proliferation is considered an essential part of Wallerian degeneration after nerve damage. Laminin, an important component of the extracellular matrix and produced by Schwann cells, provides a preferred substrate for outgrowing axons. To study whether low energy (He-Ne) laser irradiation may exert a positive effect on nerve regeneration through an effect on Schwann cells, its effect was evaluated in vivo. Schwann cells were isolated from sciatic nerves of 4-5-day-old Wistar rates and cultured on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 33 publications
2
51
2
2
Order By: Relevance
“…27 In rats with blunt-impact muscle trauma, photobiomodulation therapy blocked reactive oxygen species release and activation of nuclear factor-kB, inhibited overexpression of inducible nitric oxide synthase, reduced the inflammatory response, and decreased collagen production in the traumatized muscle, compared with traumatized muscles from rats that did not undergo photobiomodulation therapy. 28 Results of in vitro studies have shown that exposure to light enhances proliferation of Schwann cells, 29 affects nerve cell metabolism, and increases neuronal sprouting and migration. [30][31][32] Moreover, in vivo and in vitro studies have shown that exposure to light causes changes in inflammatory cell migration into the injured spinal cord [33][34][35][36] and modulates microglia polarization from a proinflammatory to anti-inflammatory phenotype.…”
Section: Ivddmentioning
confidence: 99%
“…27 In rats with blunt-impact muscle trauma, photobiomodulation therapy blocked reactive oxygen species release and activation of nuclear factor-kB, inhibited overexpression of inducible nitric oxide synthase, reduced the inflammatory response, and decreased collagen production in the traumatized muscle, compared with traumatized muscles from rats that did not undergo photobiomodulation therapy. 28 Results of in vitro studies have shown that exposure to light enhances proliferation of Schwann cells, 29 affects nerve cell metabolism, and increases neuronal sprouting and migration. [30][31][32] Moreover, in vivo and in vitro studies have shown that exposure to light causes changes in inflammatory cell migration into the injured spinal cord [33][34][35][36] and modulates microglia polarization from a proinflammatory to anti-inflammatory phenotype.…”
Section: Ivddmentioning
confidence: 99%
“…38 LLLT has been also successfully employed for nerve repair and reduction of neural injury in animal models, 42 and it is clinically used to relieve pain in humans. 43 A number of secondary effects of LLLT on nervous tissue have also been described, including: (1) increased expression of the anti-apoptotic protein Bcl-2 and reduced expression of the proapoptotic protein Bax, 38 (2) decreased numbers of apoptotic cells after exposure to the amyloid beta protein, 44 (3) improved function of cortical neurons inactivated by toxins, 9,38 (4) increased survival and ATP content of striatal neurons after rotenone-and MPP + -induced toxicity and decreased oxidative stress and nitric oxide production, 40 (5) increased neurite outgrowth, 45 (6) regulation of genes encoding for DNA repair proteins, antioxidant enzymes, and molecular chaperones, 8 and (7) increased proliferation of olfactory ensheating stem cells, 39 Schwann cells, 46 astrocytes, and oligodendrocytes. 47 In vivo, LLLT induces peripheral and central nerve regeneration after trauma, 42,47,48 reduces neuroinflammation, 42 prevents methanol-induced photoreceptor degeneration, 12 and prevents retinal neurodegeneration induced by complex I inhibition.…”
Section: Effects Of Lllt On Nervous Tissuementioning
confidence: 99%
“…30 It has also been suggested that phototherapy may enhance recovery of neurons from injury by altering mitochondrial oxidative metabolism, 3 and guiding neuronal growth cones in vitro, perhaps due to the interaction with cytoplasmic proteins and, in particular, to the enhancement of actin polymerization at the leading axon edge. 4 A possible molecular explanation was provided by demonstrating an increase in growth-associated protein-43 immunoreactivity in the early stages of rat sciatic nerve regeneration after phototherapy.…”
mentioning
confidence: 99%